Bioactivity Test of Mindi Extractives (Melia azedarach Linn) Using Brine Shrimp Lethality Test - Wasrin Syafii; Rita K Sari; Siti Maemunah (Jurnal Ilmu dan Teknologi Kayu Tropis, 2014)
The aims of this research were to determine the yield of extracts from continuous extraction of heartwood, sapwood, inner bark, branch, and leave of Toona sinensis in n-hexane, ethyl acetate, and methanol solvents and their bioactivity using brine shrimp lethality test (BSLT) was evaluated. The results indicated that the yield of leave, inner bark, branch, heartwood, and sapwood extracts were 11.0, 6.7, 1.9, 1.6, and 1.6%, respectively. The highest yield of extracts was obtained from extraction in ethyl acetate (16.1%), followed by methanol (3.5%), and n-hexane (3.1%). The BSLT tests showed that the ethyl acetate extracts of all tree parts have higher bioactivities (LC50 1-52 μg ml-1) than the n-hexane extracts (LC50 40-181 μg ml-1), and the methanolic extracts (LC50 49-1375 μg ml-1). The ethyl acetate extract from inner bark has the highest bioactivity (LC50 μg ml-1). The qualitative analysis detect the ethyl acetate extract from inner bark containing saponins, alkaloids, phenolics, flavonoids, triterpenoids, steroids, and glycosides.Key words: Artemia salina, bioactivity, brine shrimp lethality test, Toona sinensis